Evaluation of Kidney Injury Molecule-1 (KIM-1) and Neutrophil Gelatinase-Associated Lipocalin (NGAL) Urinary Levels for Detecting Kidney Dysfunction in Patients With Nasopharyngeal Cancer Treated With Cisplatin-Based Treatment - Rejeki, Marliana Sri; Arozal, Wawaimuli; Setiabudy, Rianto; Atmakusuma, Djumhana (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Cisplatin has a potency of causing nephrotoxicity. Serum BUN and creatinine levels have been well-known for detecting kidney dysfunction; while KIM-1 and NGAL urine levels are relatively new measurements. The study was aimed to evaluate urinary KIM-1 and NGAL level to detect kidney dysfunction in patients with advanced stage NPC who received cisplatin-based chemotherapy.Methods: The study was a cohort-prospective study with 3 subject groups, i.e. patients who had never received and who had received 75-100 mg/m2 cisplatin-based chemotherapy as well as those who had never received 40 mg/m2 cisplatin-based chemotherapy. The levels of urinary KIM-1, NGAL and serum level of BUN and creatinine were measured before and after receiving cisplatin. Statistical analyses were ANOVA, Pearson, Spearman, Kolmogorov-Smirnov test and SPSS version 22.0.Result: There was a significant difference of delta BUN level (p=0.0001) and delta urinary NGAL level (p = 0.025) before and after treatment in all three groups; while delta KIM-1 level showed no significant difference in all three groups (p=0.275). Cisplatin may cause accumulated nephrotoxicity, which has dose-dependent manner.Conclusion: Measuring urinary NGAL level can detect an early stage of kidney dysfunction; however, it still cannot replace the role of BUN. Measurement of urinary KIM-1 level cannot detect kidney dysfunction.